Adaptive Computations in the Uintah Framework - Luitjens, Justin; Guilkey, James; Harman, Todd; Worthen, Bryan; Parker, Steven G. (Advanced Computational Infrastructures for Parallel and Distributed Adaptive Applications, 2009)
This chapter contains sections titled: Introduction Uintah Overview AMR Support Load Balancing AMR Applied to a Multimaterial Eulerian CFD Method Results Conclusions and Future Work References